2010
DOI: 10.1007/s11934-010-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Urinary Incontinence and Its Treatment on Female Sexual Function

Abstract: Urinary incontinence is a prevalent disorder that negatively impacts not only women's overall quality of life but also female sexual function. Most of the literature suggests that women with urge urinary incontinence are more likely to report sexual complaints and dissatisfaction than women with stress urinary incontinence. Successful treatment of both stress urinary incontinence and urge urinary incontinence have been shown to improve overall female sexual function scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
3
11
1
Order By: Relevance
“…Therefore, we used the GRISS to determine the quality of sexual life and the existence and severity of sexual problems affected by USI, UUI, and UMI. Our study results showed that infrequency, dissatisfaction, avoidance, and anorgasmia but not non‐communication, nonsensuality, or vaginismus were significantly higher in the UI group compared with the control group; these results were consistent with those of other studies, suggesting a deterioration of sexual life . In order to determine QoL and distress in our study, when we investigated incontinence subtypes, dissatisfaction was observed at a higher rate in women with UMI and scores of the UDI‐6 and IIQ‐7 were also higher in the UMI group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, we used the GRISS to determine the quality of sexual life and the existence and severity of sexual problems affected by USI, UUI, and UMI. Our study results showed that infrequency, dissatisfaction, avoidance, and anorgasmia but not non‐communication, nonsensuality, or vaginismus were significantly higher in the UI group compared with the control group; these results were consistent with those of other studies, suggesting a deterioration of sexual life . In order to determine QoL and distress in our study, when we investigated incontinence subtypes, dissatisfaction was observed at a higher rate in women with UMI and scores of the UDI‐6 and IIQ‐7 were also higher in the UMI group.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have suggested that USI has the greatest impact on sexual life . Detrusor instability or urgency was found to cause greater deterioration in sexual‐health‐related QoL than other subtypes of UI . In parallel with our study results, other authors concluded that mixed UI had a significant impact on sexual function compared with other types of UI …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…did not report on severity of symptoms, it is unclear whether the difference in prevalence of urinary incontinence during sexual intercourse between their study and ours can be attributed to this. In addition, it is unclear whether different types/levels of severity of urinary incontinence influence the degree of impact of urinary incontinence on sexual functioning; the literature on this topic is conflicting [6]. Moreover, Oh et al.…”
Section: Discussionmentioning
confidence: 99%